Pengembangan Asesmen Kinerja Praktikum Sistem Respirasi Pada Serangga - NURHAYATI NURHAYATI; TRI AYU ASTUTI; RIZHAL HENDI RISTANTO; MIEKE MIARSYAH (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
This research is research and development (R & D) which aim to develop assesment of respiration practicum performance in insects. The development of student practicum performance instruments is only focused on measuring student’s psycomotor competencies, especially in practicum, but this research was only carried out until the validation stage was carried out by the validator. This research used 4D models which consisting of four stage define, develop, design, and disseminate. The stage of develop and disseminate are not done due to limited time. The instruments in this research is performance assesment validation sheet and performance assesment instruments sheet. The result is development of performance assesment instruments in the respiration practicum that has been validated content indicates that validation of student practicum performance instruments on indicators of filling in instruments and indicators of conformity with indicators and objectives of practicum performance assesment students show very valid criteria that have an average of 3,50. Next indicator is the language used in the practical performance assesment instrument students have valid criteria with an average of 3,33 and conformity indicator with the rubric has valid criteria with an average of 3,00. So the results of the validation of the entire instrument of practicum performance assesment students have valid criteria with an average of 3,33 and valid is used as a student practicum performance instrument. Key Words: Performance Assesment, Practice